Pacing strategy and performance during the world championship marathon race - Renfree, A.; St. Clair Gibson, A. (17th Annual Congress of the European College of Sport Science (ECSS), Bruges, 4. -7. July 2012, 2012)
Optimal pacing is fundamental to successful endurance performance. Although there appears to be a common strategy characteristic of elite performance in distance running events (Tucker et al 2006), previous research has focused on strategies employed by successful or winning athletes. The present study analysed pacing strategies of successful and less successful athletes during a championship race. Methods: Final and intermediate 5 km times of finishers (n=60) in the 2009 IAAF Women`s Marathon Championship race were accessed via the championship website along with individual personal best (PB) times. Times were converted to mean speeds (m/s). Competitors were split into four groups with Groups 1,2,3, and 4 comprising the first, second, third, and fourth 25% of finishers. Mean speed maintained in PB performances and intermediate segments of the race were calculated for all groups. Relative speed (% of PB speed) was also calculated for intermediate segments. One way ANOVA was used to identify differences in performance times, and two way ANOVA followed by the Bonferroni post-hoc test was used to identify differences between groups in intermediate segments. Results: Mean PB speed decreased from Group 1 to 4; other than between Groups 3 and 4, all differences were statistically significant (P<0.05). Speed maintained in the race was 98.5 + 1.8%, 97.4 + 3.2%, 95.0 + 3.1% and 92.4 + 4.4% of PB speed for Groups 1-4 respectively. Group 1 was fastest in all segments and displayed less variability in speed. Differences in speed between groups increased as the race progressed. Group 1 ran at a lower relative speed than other groups for the first two 5 km segments, but a higher relative speed from 35km onwards. Statistically significant differences (P<0.01) in the percentage of PB speed maintained were observed between Groups 1 and 4, and 2 and 4 in all segments after 20 km, and Groups 3 and 4 from 20-25 km and 30-35 km. Discussion: Group 1 athletes displayed strategies that resulted in superior relative performances. It appears that Group 2, 3, and 4 athletes selected unsustainable initial speeds that resulted in losses of speed later in the race. Although it is only possible to speculate as to the mechanisms underpinning selection of initial work rates, it may be that psychological factors specific to a major competitive event influenced decision making by athletes. These poor decisions resulted in performances inferior to those that may have been expected based on PB times. Further research is warranted to examine the decision making process leading to selection of pacing strategies in competitive events.